Effect of microscopic aggregation behavior on polymer shear resistance. Issue 19 (6th November 2019) - Shi, Leiting; Zhu, Shijie; Ye, Zhongbin; Xue, Xinsheng; Liu, Changlong; Lan, Xitang
ABSTRACT: The study of polymer aggregation behavior effect on shear resistance shed light on the synthesis of antishear polymer for oil displacement and enhances the application effect of polymer flooding. The effects of mechanical degradation on the properties of polymer solutions were studied by using partially hydrolyzed polyacrylamide (HPAM), hydrophobically modified HPAM (HMPAM), and dendritic hydrophobic associative polymers (DHAP), which are characterized by "granular, " "chain, " and "cluster" aggregation behavior, respectively. The results show that mechanical shearing can dramatically reduce the performance of polymer solution. The shearing resistance can be effectively enhanced by improving the polymer aggregation behavior. After being strongly sheared, hydrophobically associating polymers can still partially restore its network through hydrophobic association, therefore rebuild the solution viscosity. For DHAP, the broken molecular chains distribute more evenly in solution after shearing. In addition, the strength of reconstructed network structure of DHAP is better than that of HMAPM, which implies a better shear resistance. Furthermore, the hydrophobic association of linear polymers will increase their static adsorption on quartz sand. Meanwhile, DHAP with stronger spatial structure has less static adsorption, which is beneficial to maintain a higher polymer concentration in solution. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2019, 137, 48670. Abstract :